Penggunaan Algoritma Backtracking Pada Permainan Knight's Tour Dengan Membandingkan Algoritma BFS Dan DFS - Refan Rahmat Fauzi; Mochammad Taufik Faturrohman; Raihan Samhari (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2023)
Knight is one type of pawn in the game of chess. By using a strategy to play chess pieces, the rules of the Knight's Tour are formed. Knight's Tour is a math puzzle where we have to move the piece by forming the letter "L" exactly once on the game board. Progression in the game results in different types of moves in the Knight and solutions provided. The goal is to get every possible move on the Knight in completing the game optimally. There are various algorithm methods that have been developed to solve this game, one of which is the Backtracking algorithm. And in this study, researchers produced a comparison between the BFS and DFS algorithms in completing the knight's tour game.